Effects of Health Messages on Knowledge, Satisfaction, and Anxiety of Patients' Companions Referring to Tehran Heart Center - Monir Sadat Akhlaghi; Mohammad Javad Zahedi; Shirin Ahmadnia (Hamadan University of Medical Sciences, 2018)
Background and Objectives: One of the most important concerns of health care professionals is information. This study was conducted with the aim of investigating the effects of health-message broadcast via the closed-circuit television (CCTV) system of the waiting lounge of Tehran Heart Center (THC) on knowledge, satisfaction, and anxiety of patients. Materials and Methods: In this quasi-experimental study, 196 patients' companions were selected by the available sampling method in 2017. The intervention tool was a 17-minute video about cardiovascular disease displayed at a certain time in the THC waiting lounge. The data were collected by the Spielberger's State-Trait Anxiety Inventory before and after the intervention and a researcher-made questionnaire on the levels of satisfaction and knowledge after the health-message broadcast. The data were analyzed by the SPSS 22 software, using paired t-test and Pearson correlation coefficient. Results: There was a positive and significant correlation between the knowledge (r=0.480) and satisfaction (r=0.375) of individuals from health messages and the quality of the content of health messages (p=0.001). There was a significant difference between the mean scores of participants' anxiety before and after intervention (p<0.001), indicating the effect of intervention on reducing their anxiety levels. Conclusion: The strategy of broadcasting health messages on the CCTV of the THC waiting lounge is effective in improving the levels of knowledge, satisfaction, and anxiety of the patients' companions and can be of help in protecting and making them participate in patient care and even prevention.